CONNECTING IN CAPE YORK: EXPLORING DIGITAL INCLUSION AND ACCESS FOR LOW INCOME INDIGENOUS FAMILIES - Rogers, Jessa; Marshall, Amber; Osman, Kim (AoIR Selected Papers of Internet Research, 2023)
Our presentation will discuss how our team of Indigenous and non-Indigenous developed a unique Indigenous research methodology to increase understanding of the digital inclusion challenges faced by low income Indigenous families living on Mornington Island, a remote Aboriginal community in remote Queensland, Australia. We discuss our methodology and findings of how low income Mornington Island Aboriginal families use the internet to access government and social services, education, e-health and e-commerce. This project employs Indigenous methodologies including yarning, participant photography, and co-design workshops to inform policies, practices and programs. Our results are interpreted within the growing body of decolonizing methodologies and Indigenous research, methods and methodologies. Informed by Martin’s (2009) Relatedness Theory, our data is considered through Aboriginal ways of being, doing and knowing, with Aboriginal axiology, epistemology and ontology forming a window through which we observe, analyse and interpret data. In this presentation, we will discuss how we as a blended research team: • facilitated Indigenous involvement in the research (starting with the development of the research concept and design) • engaged strongly with with Indigenous research and literature, both academic and community-based to interpret data and findings • engaged with and developed Indigenous methodologies to ensure the effectiveness and appropriateness of this research and • represented Indigenous authors and voices in analysis and communication of research results